Words in action: investigating students' language acquisition and emotional performance through embodied learning. Issue 4 (7th August 2020) - Kosmas, Panagiotis; Zaphiris, Panayiotis
ABSTRACT: There is strong evidence that movement and learning are deeply interlinked supporting effective cognitive functioning and thinking. The link between movement and learning constitutes a new pedagogical paradigm in the contemporary field of language learning and specifically in the area of Embodied Pedagogy and learning. Embodied theories argue that body, next to the mind, is an essential factor in the learning process providing a positive impact on children's academic growth and language development. This pedagogical concept may offer new ways of engaging students in learning by adopting teaching methods based on Embodied Cognition practice. With this in mind, a classroom movement-based learning intervention, called PanBoy, was developed for first and second graders in mainstream elementary schools. A total of 118 elementary students from six authentic classrooms, were involved in a three-month movement-based intervention in a language learning context. Findings based on statistical analysis of psychometric pre–post testing in language, in conjunction with teachers' interviews, revealed significant gains in students' academic achievements and showed improvement on students' emotional engagement in the process. This study discusses the potential of this classroom intervention, based on embodied learning, as a new teaching practice method with low-cost ideas and easy implementation in real-context language environments.